PT MD Entertainment Tbk (Film) - PT Net Visi Media Tbk (Netv) Acquisition Deal: Valuation and Financial Due Diligence - Nafis Hestopo, Dzakwan; Arif Sumirat, Erman (DINASTI RESEARCH, 2025)
This study evaluates the financial and strategic implications of PT MD Entertainment Tbk's (FILM) acquisition of an 80% stake in PT Net Visi Media Tbk (NETV). Indonesia’s creative economy, particularly the film and media sectors, presents significant growth potential, contributing substantially to GDP and employment. However, challenges such as financing constraints and the shift to digital transmission have disrupted traditional media, including NETV, which faces financial struggles. MD Entertainment, a leader in Indonesia’s film industry, pursued this horizontal acquisition to diversify into television broadcasting. This research applied methods such as Discounted Cash Flow (DCF) analysis, financial ratio evaluation, and synergy estimation to determine NETV's fair market value and the potential benefits MD Entertainment might gain. Findings highlight the acquisition’s strategic merit in strengthening MD Entertainment’s market presence and role in the creative economy. However, concerns remain over NETV's weak financial performance and the broader challenges in television advertising revenue, which is under pressure due to global economic trends and increasing competition from digital platforms. This analysis sheds light on key factors influencing mergers and acquisitions in the creative industry, offering valuable insights for stakeholders aiming to achieve financial and strategic objectives.